DETERMINAN FAKTOR YANG MEMPENGARUHI IBU RUMAH TANGGA DALAM MELAKUKAN TES IVA SEBAGAI UPAYA DETEKSI DINI KANKER SERVIKS - Khosidah, Amik; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: DETERMINANS OF FACTOR AFFECTING BEHAVIOR WOMAN OF FERTILE AGE EFFORTS AGAINST CERVICAL CANCER EARLY DETECTION TEST METHODS IVA (VISUAL INSPECTION ACETIC ACID). Indonesian Cancers Foundation State that each year about 500.000 women who are diagnosed with cervical cancer and more than 250.000 died. a total of 2,2 milion women in the world suffer from cervical cancers. This research is to identify determinan factor that influence behaviour of WUS for early detection of cervical cancers with a tes method IVA (Visual Inspection With Acetic Acid) in the district of West Purwokerto Banyumas Regency. The study is quantitative research design with cross sectional exsplanatory research. The numbers of respondents as many as 100 people, where the sampel is taken by quota sampling of all cervical cancer patients and by using the formula Slovin. Data analysis is univariate, bivariate, and multivariate logistic regression using SPSS programe. There was a significant relationship between the level of knowledge about cervical cancer (p = 0.003), the level of knowledge about IVA test (p = 0.005), attitude WUS (p = 0.003), the benefits of IVA test (p = 0.033). Â  Â Keyword: Women of fertile age, cervical cancer, behavior of IVA Test